Sourcing gesture and meaning from a music score: Communicating techniques in music teaching - Blackburn, Andrew (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
Music scores carry multiple strands of information, both simultaneous and sequential. A score is a set of instructions for the performance of specific tones, pitches and durations. In the music teachers‟ studio, teachers and students take this information and „reverse engineer‟ appropriate gestures to re-create the composer‟s instructions using notation (Tormey p.2). Gestures may be explicitly present within the score - musical and visual. Through discourse with the score, student and teacher learn to become a conduit and contributor of musical ideas, through performance to an audience. In this article, two graphically notated, pipe organ works are considered from the perspective of the performer: Ligeti‟s „Volumina‟ (1961-2) and Harvey‟s „Eight Panels‟, (2007-9). Each work requires a different stance in preparation to make sense of the musical experience. The scores graphically show the gestures required to performatively re-animate each piece. This is a highly efficient and a precise teaching model, vital in the music teaching studio for understanding both explicit and implicit paradigms of instrumental performance.